The influence of psychological factors on investment decision making - Utari, Della; Wendy, Wendy; Azazi, Anwar; Giriati, Giriati; Irdhayanti, Efa (Institute of Computer Science (IOCS), 2024)
Income from investments is an issue of great interest for investors; consequently, there are a great number of individuals who are interested in investing, and it is critical to investigate factors that can influence investment decision-making to maximize profits. The investment decision-making process determines how steadfast, focused, and persistent a person is in achieving their goals. It encourages individuals to communicate their decisions by presenting various information through social media, thus influencing investor psychology in making diverse analytical decisions. This research analyses investment decisions influenced by demographic potential and psychological factors such as Social Influence, Fear of Missing Out (FOMO), Herding Behavior, and Overconfidence in investment decision-making to individuals or groups. Population data was collected in the research using a sampling method using a non-probability sampling approach to several individuals based on investment experience and a tendency to use social media related to investment through an online survey involving 200 respondents scattered across Indonesia, analysis of the research data using SPSS software. The study reveals that psychological factors, specifically Social Influence, Fear of Missing Out (FOMO), Herding Behavior, and Overconfidence, have a significantly and positively impact on investment decision-making. These findings underscore the crucial role of psychological aspects in investment decisions, providing a deeper understanding of investor behavior in an investment environment increasingly digitized by social media.